Produção de quitina, quitosana e biossurfactante, por Cunninghamella elegans UCP/WFCC 0542 em meio suplemento com residuários agroindustriais - Souza, Daniele Gilvanise de (2015)
One of the biggest challenges in biotechnological production is to produce high value-added products at a low cost. In this context, the filamentous fungus Cunninghamella elegans presents in its cell wall large amounts of chitin and chitosan, but is also able to produce biosurfactants. Chitin and chitosan has a vast field of biotechnological applications, and the bioremediation has been used in the removal and recovery of different waste, pollutant biotransformation and textile effluent discoloration. These biopolymers have linear structures with monomeric units β-1,4-N-acetyl-D-glucosamine and β-1,4-D-glucosamine, respectively. Furthermore, the surfactants are compounds synthesized by micro-organisms having properties such as reducing surface and interfacial tension, emulsification, solubilization and dispersion phases, being widely applied in the petrochemical industry. Studies with C. elegans UCP/WFCC 0542 were performed in order to evaluate their biotechnological potential for the production of chitin, chitosan and biosurfactant with the use of agroindustrial residues (corn steep liquor and soybean oil waste), using a central composite design rotational 2². The biopolymers chitin and chitosan were obtained by alkali-acid treatment with 1M sodium hydroxide, and subsequent use of 2% acetic acid. The surface-active properties of the biosurfactant were evaluated by measuring the surface tension of the metabolic liquid cell-free. Biomass production by C. elegans was 8.12 g/L with yields of 0.095 mg/g chitin and 0.036 mg/g of chitosan with a deacetylation degree of 87.44% in the proposed condition. The biosurfactant obtained in condition 8 of planning with 2.15% of corn steep liquor and 5.22% soybean oil waste has demonstrated the best surface tension with 28.20 mN/m-1 and showed stability against to different environmental conditions, having anionic character and its preliminary biochemical composition suggests that the isolated biosurfactant consists of proteins and lipids. Also this proved effective in the removal of petroleum derivatives hydrophobic compounds, removing 55.15% of motor oil, 71.42% of crude petroleum, 77.46% of kerosene and 96.41% of diesel oil in sand beach. Biosurfactant toxicity tests with Brassica oleracea seeds proved their non-toxic nature. The results show the biotechnological potential of C. elegans from alternative and low cost agroindustrial substrates, allowing its use in bioremediation process in environmental recovery.